2018
DOI: 10.3762/bjoc.14.253
|View full text |Cite
|
Sign up to set email alerts
|

An overview on recent advances in the synthesis of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials and their catalytic applications in chemical processes

Abstract: This review article discusses the progress related to the synthesis and catalytic applications of sulfonated organic materials, sulfonated silica materials, and sulfonated carbon materials for industrial and laboratory products. These catalysts are widely used in acid-catalyzed processes. Most of these acid catalysts are eco-friendly, reusable, and stable. Moreover, the discovery of unique catalysts is vital for developing new, efficient, and reusable catalysts for industrial and laboratory applications. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 79 publications
(69 reference statements)
0
32
0
Order By: Relevance
“…Graphene, one of the allotropes of carbon, is twodimensional monolayers of carbon atoms arranged in a honeycomb lattice that can be functionalized easily with acidic moieties to give new materials that can be used in acid-catalyzed processes. [1] It possesses unique physical properties, such as high thermal and electronic conductivity, high thermal stability, and high structural strength, [2][3][4] and therefore has diverse applications in various fields such as electrochemical sensors, [5] composite materials, [6] and energy technology. [7] Graphene is easily produced from graphene oxide (GO) by reduction using reducing agents such as NaBH 4 [8] or hydrazine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, one of the allotropes of carbon, is twodimensional monolayers of carbon atoms arranged in a honeycomb lattice that can be functionalized easily with acidic moieties to give new materials that can be used in acid-catalyzed processes. [1] It possesses unique physical properties, such as high thermal and electronic conductivity, high thermal stability, and high structural strength, [2][3][4] and therefore has diverse applications in various fields such as electrochemical sensors, [5] composite materials, [6] and energy technology. [7] Graphene is easily produced from graphene oxide (GO) by reduction using reducing agents such as NaBH 4 [8] or hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…12-(4-Methoxyphenyl)-9,9-dimethyl- 8,9,10,12-tetrahydrobenzo[a]xanthen-11-one (4 k)1 H NMR (300 MHz, DMSO-d 6 , ppm): δ = 0.91 (s, 3H, CH 3 ), 1.08 (s, 3H, CH 3 ), 2.14 (d, J = 16.5 Hz, 1H, one proton of diastereotopic protons in CH 2 ), 2.35 (d, J = 16.5 Hz, 1H, one proton of diastereotopic protons in CH 2 ), 2.65 (AB q , Δν = 30.0 Hz, J AB = 17.3 Hz, 2H, CH 2 ), 3.64 (s, 3H, OCH 3 ), 5.54 (s, 1H, pyran CH), 6.76 (d, J = 8.7 Hz, 2H, arom-H), 7.20 (d, J = 8.7 Hz, 2H, arom-H), 7.41-7.54 (m, 3H, arom-H), 7.90-7.95 (m, 2H, arom-H), 8.05 (d, J = 8.3 Hz, 1H, arom-H); IR (KBr, cm −1 ) υ = 2951, 1648, 1511, 1460, 1378, 1229, 1174, 1028, 832, 750. 3.6.5 | 12-(4-Hydroxyphenyl)-9,9-dimethyl-8,9,10,12-tetrahydrobenzo[a]xanthen-11-one (4 l) 1 H NMR (300 MHz, DMSO-d 6 , ppm): δ = 0.91 (s, 3H, CH 3 ), 1.07 (s, 3H, CH 3 ), 2.14 (d, J = 16.1 Hz, 1H, one proton of diastereotopic protons in CH 2 ), 2.34 (d, J = 16.1 Hz, 1H, one proton of diastereotopic protons in CH 2 ), 2.63 (AB q , Δν = 29.2 Hz, J AB = 17.4 Hz, 2H, CH 2 ), 5.48 (s, 1H, pyran CH), 6.58 (d, J = 8.5 Hz, 2H, arom-H), 7.09 (d, J = 8.5 Hz, 2H, arom-H), 7.41-7.54 (m, 3H, arom-H), 7.88-7.94 (m, 2H, arom-H), 8.05 (d, J = 8.3 Hz, 1H, arom-H), 9.20 (s, 1H, OH); 13 C NMR (75 MHz, DMSO-d 6 , ppm): δ = 26.…”
mentioning
confidence: 99%
“…[15] On the other hand, researchers found that the addition of sulfonated acidic group onto the heterogeneous or homogenous catalysts increased the acidity of the catalyst. [16] Demanding to benefit from the aforementioned significant properties of ILs, as well as the presence of strongly acidic groups, lead to emerge brønsted ionic liquid. They are non-volatile, noncorrosive, and mostly used as catalysts in organic syntheses to overcome the drawbacks of their classical homogenous inorganic counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some types of sulfonated acid catalysts have been used for xylose conversion to furfural, such as SO3H-KIT catalyst and especially 0.2-SO3H-KIT-6 [17] , carbon-based solid acid catalyst prepared from cellulose, hemicellulose and lignin containing furfural residue with acidity of 2.1-3.5 mmol/g [18] demonstrated their efficiency and feasibility in the conversion of pentoses into furfural. [12,19] Using solid acid catalyst produced from lignocellulosic biomass for production of furfural and other valuable products from the same biomass source is a sustainable chemical process with high feasibility. This work aims to utilize Acacia mangium wood waste -an abundant residue of Vietnam's paper industry -for fabrication of a carbon-based solid acid catalyst.…”
Section: Introductionmentioning
confidence: 99%